ADHD diagnosis and methylphenidate consumption in children and adolescents: A systematic analysis of health databases in France over the period 2010–2019 - Ponnou, Sébastien; Thomé, Benoît (Frontiers in Psychiatry, 2022)
Context ADHD is the most common mental disorder in school-aged children. In France, methylphenidate is the only drug authorized for ADHD. Here, we describe the pattern of ADHD diagnosis and methylphenidate prescription to children and adolescents from 2010 to 2019. Methods We conducted a retrospective cohort study of all beneficiaries of the French general health insurance scheme (87% of the population, 58 million people). We extracted information for all children and adolescents aged 0–17 years who received: (1) A diagnosis of ADHD (34,153 patients). (2) At least one methylphenidate prescription (144,509 patients). We analyzed the clinical, demographic, institutional, and social parameters associated with ADHD diagnosis and methylphenidate consumption in France. Results The ADHD diagnosis among children and adolescents increased by 96% between 2010 and 2019. ADHD diagnosis affects more boys than girls. About 50.6% of children hospitalized with a diagnosis of ADHD in 2017 also had another psychiatric diagnosis. The rate of children hospitalized with an ADHD diagnosis and treated with MPH varied between 56.4 and 60.1%. The median duration of MPH treatment for a 6-year-old ADHD child initiated in 2011 is 7.1 years. In 2018, 62% of ADHD children were receiving at least one psychotropic medication. Between 2010 and 2019, methylphenidate prescription increased by +56% for incidence and +116% for prevalence. The prevalence of methylphenidate prescription reached between 0.61 and 0.75% in 2019. Boys are predominantly medicated. The median duration of treatment among 6-year-olds in 2011 was 5.5 years. The youngest children received the longest treatment duration. Diagnoses associated with methylphenidate prescription did not always correspond to the marketing authorization. Among children receiving the first prescription of methylphenidate, 22.8% also received one or more other psychotropic drugs during the same year. A quarter of initiations and half of renewals were made outside governmental recommendations. Educational and psychotherapeutic follow-up decreased from 4.1% in 2010 to 0.8% in 2019. French children and adolescents, who were the youngest in their class were more likely to be diagnosed (55%) and prescribed methylphenidate (54%). Children from disadvantaged families had an increased risk of ADHD diagnosis (41.4% in 2019) and methylphenidate medication (25.7% in 2019).